Characteristic of Referral Patients With Severe Preeclampsia In Surabaya - Myrna Evanda Adeline; Muhammad Ardian Cahya Laksana; Atika Atika (Biomolecular and Health Science Journal, 2018)
Introductions: Pre-eclampsia is a hypertensive disorder of a pregnancy that remains major maternal mortality in developing country. Severe pre-eclampsia needed an advanced medical treatment since it could cause life treathening condition for both mother and fetus. The purpose of this research was to understand and got the  picture of the age, parity, complication, delivery method, referral pathway, age of pregnancy, birth weight, and Apgar score of baby from pre-eclamptic mother in dr. Soetomo General Hospital during 2011.Methods: This research is a retrospective-descriptive research which observed the age, parity, complication, delivery method, referral pathway, age of pregnancy, birth weight, and Apgar score of baby from pre-eclampsia mother This research used medical record then the data was recorded and analyzed  descriptively.Result: The number of patients who met the inclusion criteria were 239 patients. Patient’s age were distributed unimodally with a peak at productive age. Most of patients had previous history of pregnancy. Pulmonary edema was the most common cause of maternal complication and intra uterine fetal death was the most common cause of fetal complication. Most delivery were performed in Sectio Caesaria method. Almost all cases was direct refferal cases from other medical services. Then most of cases was reaching aterm periode. Most of babies were born with body weight ≥ 2500 gram. And based on Apgar score the babies were well adapted.Conclusions: Most of the patients with severe preeclampsia referrals were referred from a health care setting, only a small percentage of women were referred to relay. Most of severe preeclampsia occured in women with their gestational age has reached 37 weeks.